Study Of Punch-Die Misalignment Using Machine Vision System - Basir, Mohd Fairdaous (Universiti Sains Malaysia, 2017)
Misalignment is one of the main sources of defect in deep drawing process. This will delay the whole process in a production line, lead to many problem such as late of product delivery. This study investigate the punch-die misalignment using image processing system and machine vision system. The misalignment of the punch-die are obtained by analyzing the image captured using image processing system. The punch-die was placed on hydraulic press machine. Speed lights and LED lights were placed behind the specimen to capture a good quality image to be processed on MATLAB. The captured images were analyzed using image processing. Compared with the usual ways of detecting misalignment combined with the purposed image processing system has significant potential for decreasing the time consumption on fixing the misalignment.